Why is Exposure to Nature Important in Early Childhood? - Kristen R. Poppell; Martha C. Monroe (EDIS)
Early childhood is a crucial period for the physical and cognitive development of children. Most people who care for young children realize that children benefit from playing outside, but caretakers might not have ready access to the literature that supports their observations. This 4-page fact sheet reviews some of the literature that shows that young children need to go outside and be around nature regularly. It describes some of the benefits children (and adults!) gain from learning and playing outdoors and includes suggestions for several resources for parents, teachers, and caretakers who hope to increase these opportunities for their youngsters. Written by Kristen Poppell and Martha C. Monroe, and published by the School of Forest Resources and Conservation, October 2015.